Advancements and challenges in gender equity in British policing - Laverick, Wendy; Joyce, Peter; Cunningham, Emma (Policing Insight, 2023)
A series of recent reviews and reports have highlighted issues around misogyny and gender inequality in UK policing; in this article, Laverick, Joyce and Cunningham explore the context of some of those issues, and consider the advances as well as the continuing challenges in relation to gender equity in British policing.